Fire frequency, intensity, and burn severity in Kalimantan’s threatened Peatland areas over two Decades - Schmidt, Andres; Ellsworth, Lisa M.; Boisen, Grace A.; Novita, Nisa; Malik, Anjelita; Gangga, Adi; Albar, Israr; Dwi Nurhayati, Ati; Putra Ritonga, Rasis; Asyhari, Adibtya; Kauffman, J. Boone (Frontiers in Forests and Global Change, 2024)
Kalimantan, the Indonesian portion of the Island of Borneo, has an estimated 45,000 km 2 of tropical peatland and represents one of the largest stocks of tropical peat carbon. However, over the last three decades, the peatlands of Indonesia, and Kalimantan in particular, have been heavily degraded or destroyed by drainage of peatland swamps, deforestation, land cover change for agriculture, and intentional burning. Many studies have examined degradation of peat forests and the associated frequency of fires, often focusing on specific regions of Kalimantan over limited periods. Here, we present our results of a spatially comprehensive, long-term analysis of peatland fires in Kalimantan over more than two decades from early 2001 to the end of 2021. We examined the effects of changing climate conditions, land cover change, and the regulatory framework on the total burned area and frequency and severity of peatland fires over a 21-year period by combining extensive datasets of medium-resolution and high-resolution satellite imagery.Moreover, surface fire intensity was modeled for four dominant land use/land cover types to determine how land use change alters fire behavior. Our results confirm a consistent and strong spatiotemporal correlation between hydro-climatological drivers associated with El Niño conditions on peatland fire frequencies and burned peatland area. Changes in the number of fires and burn severity are visible over time and are caused by a combination of large-scale meteorological patterns and changing regulations. A significant relative increase of the 'high' and 'very high' severity across all peatland fires in Kalimantan was found for the latest period from 2015 through 2021 by 12.1% and 13.4%, compared to the two previous 7-year periods from 2001 to 2007 period and from 2008 to 2014, respectively whereas the total peatland area burned decreased in 2015 to 2021 by 28.7% on average compared to the previous periods. The results underline the importance of a comprehensive approach considering physical aspects of overarching climate conditions while improving political and regulatory frameworks to mitigate the negative effects of burning tropical peatlands.